Cold sintering of soda-lime glass. (February 2021) - Karacasulu, Levent; Ogur, Ezgi; Piskin, Cerem; Vakifahmetoglu, Cekdar
Abstract: Ordinary recycled soda lime glass powder was densified via cold sintering process with the aid of concentrated NaOH solution. Increase in processing time, temperature and concentration of the NaOH solution resulted in the formation of monolithic glass artifacts with higher relative densities. The sample densified the most (95.2%) was obtained when the sintering was performed at 250˚C with a 20 min dwell time using 15 M NaOH solution. Graphical abstract: Image, graphical abstract